2018
DOI: 10.4102/sajim.v20i1.894
|View full text |Cite
|
Sign up to set email alerts
|

Integration of social media with healthcare big data for improved service delivery

Abstract: Background: In the last decade, social media users across the world have crossed 1 billion, making it one of the fastest growing sources of big data. Also, people needing healthcare continue to increase in every society. Through accessibility, communication and interaction between health practitioners and patients, this type of ever-growing, social media subscriber–based platform can be of significant use in improving healthcare delivery to society. However, users encounter serious challenges in their attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…He is an LTD Sprint and Boeing Welliver Fellow. Figure 1 Factors influencing social media and healthcare big data [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He is an LTD Sprint and Boeing Welliver Fellow. Figure 1 Factors influencing social media and healthcare big data [7].…”
Section: Resultsmentioning
confidence: 99%
“…Big data is driving the development in biomedical and healthcare informatics because big data has unlimited potential for storing, processing, and analyzing medical data. Factors influencing social media and healthcare big data is shown in Figure 1 [7] BENEFITS Using social media allows the patients to have twoway communication with other patients and healthcare providers. It can connect individuals around the globe who share the same health conditions [8].…”
Section: Applicationsmentioning
confidence: 99%
“…The findings showed that social media challenges were the quick spread of incorrect information as well as compromised security for Internet users. A study showing the role of social media in South Africa explored social media contributions on communication and interaction between health practitioners and patients; this type of ever-growing, social media subscriber-based platform can be of significant use in improving healthcare delivery to society [59]. The study also proposed a framework to guide integration of social media with healthcare Big Data through which service delivery to patients can be improved.…”
Section: Discussion and Implications For Research In Africamentioning
confidence: 99%
“…In recent years, there has been increase in the use of BDA tools, which can be attributed to the values that are associated to the concept [7]. Grover et al suggest that the concept of BDA can be used to promote productiveness and decision-making, which brings forth to organisations [23].…”
Section: Value Of Big Data Analytics In Organisationsmentioning
confidence: 99%
“…Organisations adopt big data concept to get some insights into the data to predict the future. Many organisations employ big data with the intention of improving activities and events such as sales, advertising, and future predictions [7]. In the process of optimising the benefits of BDA, some organisations divide it into two sections: management, which is the extraction, retrieval and storage of datasets for transformation and decision-making purposes; and as the technology tool for analysing big data [8].…”
Section: Introductionmentioning
confidence: 99%